Polymyxin B1 and E2 From Paenibacillus polymyxa Y-1 for Controlling Rice Bacterial Disease - Yi, Wenshi; Chen, Chao; Gan, Xiuhai (Frontiers in Cellular and Infection Microbiology, 2022)
To discover novel microbial pesticide for controlling rice bacterial disease, polymyxin B1 and E2 were firstly isolated from the supernatant of fermentation broth of P. polymyxa Y-1 by bioactivity tracking separation. It is shown that polymyxin B1 and E2 had remarkable in vitro inhibitory activities to Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas oryzae pv. oryzicola (Xoc) with the EC50 values of 0.19 μg/mL and 0.21 μg/mL against Xoo, and 0.32 μg/mL and 0.41 μg/mL against Xoc, respectively, which were better than those of Zhongshengmycin (0.31 μg/mL and 0.73 μg/mL) and bismerthiazol (77.48 μg/mL and 85.30 μg/mL). Meanwhile, polymyxin B1 (45.8%, 35.8% and 44.8%, 39.8%) and E2 (41.2%, 37.0% and 42.9%, 39.9%) exhibited good protection and curative activities to rice bacterial blight and rice bacterial leaf streak. Polymyxin B1 exerted the anti-pesticide properties via destroying the cell integrity of Xoo, reducing its infectivity and enhancing rice resistance against pathogens through activating the phenylpropanoid biosynthesis pathway of rice. It is indicated that polymyxin B1 and polymyxin E2 were potential microbial pesticides for controlling rice bacterial disease.